Politically smart, locally led development - Booth, David; Unsworth, Sue (ODI, 2014)
Aid donors have found it hard to move from thinking politically to wor king differently, but there is evidence that they can do so and that t his improves outcomes. This paper presents seven examples of where ado pting a politically smart, locally led approach has led to better outc omes.
Keywords: Practice